Neurophysiological correlates of memory change in children with fetal alcohol spectrum disorders treated with choline - Fuglestad, Anita J.; Miller, Neely C.; Fink, Birgit A.; Boys, Christopher J.; Eckerle, Judith K.; Georgieff, Michael K.; Wozniak, Jeffrey R. (Frontiers in Psychology, 2022)
Background: Prenatal and early postnatal choline supplementation reduces cognitive and behavioral deficits in animal models of Fetal Alcohol Spectrum Disorder (FASD). In a previously published 9-month clinical trial of choline supplementation in children with FASD, we reported that postnatal choline was associated with improved performance on a hippocampal-dependent recognition memory task. The current paper describes the neurophysiological correlates of that memory performance for trial completers. Methods: Children with FASD (N=24) who were enrolled in a clinical trial of choline supplementation were followed for nine months. Delayed recall on a 9-step elicited imitation task (EI) served as the behavioral measure of recognition memory. Neurophysiological correlates of memory were assessed via event-related potentials (ERP). Results: Delayed recall on EI was correlated with two ERP components commonly associated with recognition memory in young children: middle latency negative component (Nc amplitude; range: r = -.41 to r = -.44) and positive slow wave (PSW area under the curve; range: r = -.45 to r = -.63). No significant ERP differences were observed between the choline and placebo groups at the conclusion of the trial. Conclusions: Although the small sample size limits the ability to draw clear conclusions about the treatment effect of choline on ERP, the results suggest a relationship between memory performance and underlying neurophysiological status in FASD. This trial was registered at https://clinicaltrials.gov/ct2/show/NCT01149538.